Adipocyte browning and higher mitochondrial function in peri-adrenal but not subcutaneous fat in pheochromocytoma - Vergnes, Laurent; Davies, Graeme R.; Lin, Jason Y.; Yeh, Michael W.; Livhits, Masha J.; Harari, Avital; Symonds, Michael E.; Sacks, Harold S.; Reue, Karen (Endocrine Society, 2016)
Context: